Tinjauan Hukum Islam Pada Jual Beli Akun Game Online Mobile Legends Di Kabupaten Garut - Syaripudin, Enceng Iip; Auliaulhikmah, Muhammad (STAI Al Musaddadiyah Garut, 2022)
Buying and selling online game accounts can be done directly or online, as for the details and flow of transactions in sequence, researchers still do not know before meeting facts in the field. In buying and selling game accounts if done online there is a possibility of mistrust between the seller and the buyer, this in Islamic law is certainly not appropriate where there should be mutual trust and pleasure between the seller and the buyer. This study aims to find out and describe the buying and selling of mobile legends online game accounts in terms of thoughts or theories that state that buying and selling is exchanging assets for treasures using certain methods or exchanging something desired with the value of commensurate objects through certain useful ways. Buying and selling mobile legends online game accounts is a buying and selling activity to gain profit from each other (mobile legends online game account users). The method used in this study is a type of library research, namely by conducting research on written sources, then this researcher is qualitative. This study aims to collect information or data about the phenomenon studied, namely the review of Islamic law on buying and selling mobile legends online game accounts in Garut Regency. Based on the results of the study, it can be concluded that in a review of Islamic law on buying and selling mobile legends online game accounts in Garut Regency. The transaction method is carried out to both parties, namely the seller and the buyer, sometimes using a third party called a rekber (joint account), but in this transaction there is a fraud, such as fraud committed when the account that is the object of buying and selling is not as expected and also fraud such as not handing over the account to the buyer after making a payment. Viewed from the pillars of buying and selling according to Hanafiyah Ulama, Jumhur Ulama, and the Compilation of Sharia Economic Law Book II article 22 along with its legal requirements have fulfilled as a category of buying and selling bay' as-Salam where the buyer makes payment in advance with dependent goods by the seller. But if the harmony and legal conditions of the sale and purchase are damaged (fasid), So the trade is not legal, such as the element of fraud in buying and selling accounts in the Mobile Legends online game. Keywords: Islamic Law, Buy and Sell Online Games, Mobile Legends